PENGARUH PELATIHAN TERHADAP PRODUKTIVITAS GURU PNS PADA SMPN 15 KOTA JAMBI - Anisah Anisah (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
This research entitled “Influence of Training Upon Productivity of Government Teachers in SMPN 15 Kota Jambi”. Objectives of this research are to know the training activity, and productivity of the teachers. Survei was used as method of this research. The data was collected by using questioner which given to every government teachers. For analizing data, verificative method was used to proof that training influence upon productivity of the teachers. Influence of training upon the teachers productivity were analized by means of simple  regression. The result of this research shows that according to the teachers training activity and productivity of the government teachers in SMPN 15 were good. Moreover, training have influence significantly upon the teacher productivity.Keywords : Training, productivity and teacher